2008
DOI: 10.1111/j.1744-313x.2008.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

A search for cyclophilin‐A gene (PPIA) variation and its contribution to the risk of atherosclerosis and myocardial infarction

Abstract: Cyclophilin A is secreted by vascular smooth muscle cells in response to inflammatory stimuli, and could thus contribute to atherosclerosis. We hypothesized that the genetic variation at the cyclophilin A gene (PPIA) could affect the risk for developing atherosclerosis and myocardial infarction. This study included 250 myocardial infarction patients (all male and < 60 years; 95% are smokers). All these cases had at least one atherosclerotic diseased coronary vessel. DNA was obtained from patients and from 250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…Polymorphisms in the promoter region of CypA may have an effect on the CyPA expression levels and recently it was demonstrated that the 1604G allele enhances binding of transcription factors such as SP1, resulting in increased transcription of the CypA gene [25], [30]. Seemingly in contrast, we here observed a reduction in CypA expression in PBMC isolated from healthy C1604G heterozygous blood donors when compared to PBMC from carriers of the major allele.…”
Section: Discussioncontrasting
confidence: 44%
“…Polymorphisms in the promoter region of CypA may have an effect on the CyPA expression levels and recently it was demonstrated that the 1604G allele enhances binding of transcription factors such as SP1, resulting in increased transcription of the CypA gene [25], [30]. Seemingly in contrast, we here observed a reduction in CypA expression in PBMC isolated from healthy C1604G heterozygous blood donors when compared to PBMC from carriers of the major allele.…”
Section: Discussioncontrasting
confidence: 44%
“…The −11 G could mediate its pro‐nephrotoxic effect through an increased production of cyclophilin A. To confirm this hypothesis, we transfected HEK293 cells with luciferase plasmids containing the two promoters (−11 G and −11 C), and found higher promoter activity for cells transfected with −11 G. We had previously reported this functional effect in a different cell‐type (16). The −11 G has been linked to a more rapid CD4+ T‐cell loss and a more rapid progression to AIDS, compared to −11 C (CypA is incorporated into HIV‐1 virions and facilitates HIV‐1 replication in host cells) (29).…”
Section: Discussionmentioning
confidence: 78%
“…Transient transfection and reporter assays were performed to compare the activity of different alleles of PPIA promoter in driving expression, as previously reported (16). Both PPIA promoters from −578 to +69 bp relative to the transcriptional start site (ENSG00000196262) were generated by PCR using genomic DNA from an heterozygous patient (−11 G/C) and the following primers, containing Kpn I and Hind III restriction sites, respectively: forward, GCTCAAAGGTACCCTCCTTCCTGAC and reverse GACGGCAAGCTTGAAGAACACGG.…”
Section: Methodsmentioning
confidence: 99%
“… 121 129 This protein can stimulate the immune response and is produced by inflammatory cells such as endothelial cells, monocytes, vascular smooth muscle cells, and platelets. 130 132 Extracellular CyPA, through interaction with cell membrane heparin receptor and CD147, also functions as a chemoattractant for monocytes, neutrophils, eosinophils, and T lymphocytes. 133 Like other CyPs, CyPA acts as a chaperone in the regulation of cellular protein 111 , 120 , 125 and receptor expression and activities.…”
Section: Cyclophilin Amentioning
confidence: 99%